The Influence of Transformational Leadership on Organizational Citizenship Behavior (OCB) through Innovative Work Behavior and Readiness to Change among Educational Staff at the Institut Seni Indonesia Yogyakarta - Purnomo, Tri; Subiyanto, Didik; Hadi, Syamsul (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to investigate the effect of Transformational Leadership on Organizational Citizenship Behavior (OCB) among educational staff at the Indonesian Institute of Arts Yogyakarta by examining the mediating roles of Innovative Work Behavior (IWB) and Readiness to Change (RTC). This research employs a quantitative approach, using primary data collected through structured questionnaires and analyzed using Partial Least Squares (PLS) via SmartPLS 4. The results show that Transformational Leadership has a significant positive effect on OCB, as well as on IWB and RTC. Furthermore, both IWB and RTC act as significant mediators that strengthen the relationship between Transformational Leadership and OCB. These findings imply that educational institutions, especially in higher education, can enhance staff performance and extra-role behavior by fostering transformational leadership, innovation, and change readiness. The originality of this study lies in its integrative framework that introduces IWB and RTC as mediating variables, offering new insights into how leadership shapes organizational behavior through innovation and adaptability mechanisms.